Analisis Pelaksanaan Pembelajaran Daring di Masa Pandemi Covid-19 Pada Guru Mata pelajaran IPA di SMP Kota Jambi: (Analysis of the Implementation of Online Learning during the Covid-19 Pandemic for Science Subject Teachers at Jambi City Junior High School) - Ema Faorika; Afreni Hamidah; Evita Anggereini (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2021)
Learning in schools is carried out online in Jambi City. This is done to prevent the spread of the Covid-19 virus. The purpose of the study was to analyze the implementation of online learning and find out the obstacles encountered by science subject teachers in Jambi City Junior High Schools during online learning. This type of research is a mixed method using an explanatory mixed method research design. Researchers distributed survey questionnaires via google form to respondents and conducted interviews via whatsapp. The data were analyzed using SPSS to determine the validity and reliability with the Cronbach alpha test. The results showed that the implementation of online learning during the COVID-19 pandemic for science subject teachers at Jambi City Junior High School with the online learning planning stage, the online learning process stage and the online learning assessment stage had been carried out with various obstacles during its implementation. One of the most conspicuous obstacles is that 80.36% of the teachers are digital immigrant generations so that these teachers include teachers who have limited human resources, namely lack of technology (internet) skills. Constraints encountered during the implementation of online learning are limited human resources, limited facilities and infrastructure and constraints on students' personalities. Abstrak. Pembelajaran di sekolah dilaksanakan secara daring di Kota Jambi. Hal ini dilakukan untuk mencegah penularan virus covid-19. Tujuan penelitian untuk menganalisis pelaksanaan pembelajaran daring dan mengetahui kendala yang ditemui guru mata pelajaran IPA di SMP Kota Jambi selama pembelajaran daring. Jenis penelitian adalah penelitian campuran (mix method) dengan menggunakan desain eksplanatori (explanatory mixed method research design). Peneliti menyebarkan angket survey via google form kepada responden dan melakukan wawancara via whatsapp. Data dianalisis menggunakan SPSS untuk mengetahui Validitas dan Reliabilitas dengan uji Cronbach alpha. Hasil penelitian menunjukkan bahwa pelaksanaan pembelajaran daring di masa pandemi covid 19 pada guru mata pelajaran IPA di SMP Kota Jambi dengan tahap perencanaan pembelajaran daring, tahap proses pembelajaran daring dan tahap penilaian pembelajaran daring telah dilaksanakan dengan berbagai kendala selama pelaksanaanya. Salah satu kendala yang paling mencolok adalah 80,36% guru tersebut merupakan generasi digital immigrant sehingga guru-guru tersebut termasuk guru yang memiliki keterbatasan sumber daya manusia yaitu kurang menguasai teknologi (internet). Kendala yang ditemui selama pelaksanaan pembelajaran daring yaitu keterbatasan sumber daya manusia, keterbatasan sarana dan prasarana dan kendala pada pribadi siswa.